2014
DOI: 10.2967/jnumed.114.138313
|View full text |Cite
|
Sign up to set email alerts
|

Early Biochemical Relapse After Radical Prostatectomy: Which Prostate Cancer Patients May Benefit from a Restaging11C-Choline PET/CT Scan Before Salvage Radiation Therapy?

Abstract: The aim of the study was to assess which factors may influence 11 C-choline PET/CT detection rate in a population of recurrent prostate cancer (PCa) patients listed for salvage radiation therapy (S-RT) in an early phase of biochemical relapse, to select which patients could obtain the most benefit by performing restaging 11 C-choline PET/CT before S-RT. Methods: The study comprised 605 patients, treated with radical prostatectomy (RP) with curative intent for PCa who showed rising PSA levels after primary ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 32 publications
1
63
1
3
Order By: Relevance
“…Castelluci et al reported 11C--choline PET/CT scans indicating metastases in 23% of 605 patients with PSA < 2 ng/mL, and in 18% of 291 patients with PSA < 1.0 ng/mL [15]. This is slightly less than in our study, but almost 25% of the patients in their study received HT at the time of the PET/CT investigation, which is known to affect the sensitivity of choline PET/CT [22].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Castelluci et al reported 11C--choline PET/CT scans indicating metastases in 23% of 605 patients with PSA < 2 ng/mL, and in 18% of 291 patients with PSA < 1.0 ng/mL [15]. This is slightly less than in our study, but almost 25% of the patients in their study received HT at the time of the PET/CT investigation, which is known to affect the sensitivity of choline PET/CT [22].…”
Section: Discussioncontrasting
confidence: 70%
“…Few previous studies have reported specifically on patients with low PSA values, i.e. when the choice of secondary treatment usually has to be made [13][14][15][16][17][18]. Most of the studies included a large proportion of patients on HT, for whom the association between PSA values and tumour burden is different than for hormone--naïve patients, and for whom treatment with additional RT is not evidence based.…”
Section: Introductionmentioning
confidence: 99%
“…38 Embora também pareça ter utilidade clínica no estadiamento inicial, apresenta-se como particularmente útil no restadiamento de doentes com recidiva bioquímica. 39 Revela-se principalmente vantajosa numa fase precoce da recidiva bioquímica, permitindo seleccionar os doentes que podem beneficiar de terapêutica de salvação. Revela-se, ainda, particularmente vantajosa na avaliação de doentes em recidiva bioquímica sob TSH, devido à elevada probabilidade de apresentarem doença extra pélvica.…”
Section: Discussionunclassified
“…Revela-se, ainda, particularmente vantajosa na avaliação de doentes em recidiva bioquímica sob TSH, devido à elevada probabilidade de apresentarem doença extra pélvica. 39 Vários estudos têm avaliado a acuidade diagnóstica desta técnica no contexto de recidiva bioquímica de CaP, apresentando valores de sensibilidade muito variáveis, entre 43 e 95%. 5,7,10,12,14,24,[40][41][42][43] Um estudo recente demonstrou a elevada sensibilidade e o elevado valor preditivo negativo da PET/CT com FCH-18.…”
Section: Discussionunclassified
“…However, the majority of large series have included patients with a PSA level >2 ng/ml (6,7). Most studies that included patients with low PSA levels have shown infrequent bone metastases, and little information is provided concerning tumor characteristics in individual patients (8)(9)(10)(11). Generally, choline PET is only indicated in biochemical failure if the PSA level is >2 ng/ml or the PSA level is rising rapidly (12).…”
Section: Introductionmentioning
confidence: 99%